Draft Annual Plan 2012 - 2013 Volume I - Planning Commission (Planning Commission, 2012)
Amidst the grandeur of the Himalayas, lush green valleys , the two fast flowing rivers and spread below the mighty Mount Khanchendzonga, lies the small mountain state of Sikkim. An amazing aspect of this region is the enormous altitudinal range within its topography. From a mere 300 meters above sea level, it soars up to the lofty heights of the mighty Khangchendzonga at 8598 meters, resulting in climatic zones from the tropical to the tundra. It has a total area of 7,096 sq. km extending over 112 km from North to South and 64 km from East to West. Strategically located in the Eastern Himalayas, it shares a 200 km border with Tibet, a 33 km border with Bhutan and an 85 km border with Nepal. It is bounded by the vast stretches of the Tibetan Plateau in the North; the Chumbi Valley of Tibet and the Kingdom of Bhutan in the East; Nepal in the West and the Darjeeling District of West Bengal in the South.
Development Planning Economic Reforms & North Eastern Council Affairs Department Government Of Sikkim